Analyzing the Impacts of Climate Change on the Hydrological Regime and Aquatic Biodiversity of the Danube River - Desimira Maria STROE; Angelica DOBRE; Mirela CRETU; Magdalena TENCIU; Elena Ioana COMAN; Neculai PATRICHE (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies)
Climate change presents considerable challenges to global ecosystems, particularly freshwater environments like the Danube River. This study investigates the variability in hydrological and physico-chemical parameters of the Danube River, alongside assessing changes in aquatic biodiversity indicators. Data were collected from monitoring stations in the Chiscani area, Braila County, specifically at Km 169-197. The findings reveal significant temporal trends in both hydrological and chemical parameters, with seasonal variations indicating potential impacts on aquatic ecosystems. Biodiversity indices demonstrate varied responses of aquatic communities to shifting environmental conditions. The study concludes that climate-induced changes in the Danube's hydrological regime have substantial implications for aquatic biodiversity, emphasizing the need for conservation efforts to address these challenges and ensure the river system's sustainability.